Upper and lower trunk translations associated with stepping - Crosbie, J.; Durward, B.; Rowe, P. (Gait & posture, 1996)
We conducted a series of tests to investigate the upper and lower trunk translatory motions prior to and during stepping activities. Ten male and 10 female able-bodied subjects were tested. Two pairs of orthogonally orientated linear displacement transducers measured the excursions of the sacrum and upper thorax in the horizontal plane while (a) stepping sideways and (b) stepping forward on to a kerb. We found that predictable and consistent patterns of upper and lower trunk displacement preceded and accompanied the stepping actions. We detected significant gender differences only with respect to posterior displacement of the pelvis during side stepping and lateral displacement of the upper trunk during forward stepping. We concluded that the other trunk translatory movements associated with stepping could be considered biomechanical invariants.